On characterization of B-focal curves in double-struck E sign 3 - Körpinar, Talat; Bas, Selçuk (My University, 2013)
In this paper, we study B-focal curves in the Euclidean 3-space double-struck E sign 3. We characterize B-focal curves in terms of their focal curvatures. © Soc. Paran. de Mat.
Keywords: Bishop frame; Euclidean 3-space; Focal curve